Characterization of transcripts emanating from enhancer Eβ of the murine TCRβ locus - Faizan Uddin; Madhulika Srivastava (FEBS Open Bio, 2021)
Enhancers are well established as critical regulators of gene expression, but the mechanisms underlying the molecular basis of their specificity and activity are only partly understood. One of the most exciting recent observations is the discovery of enhancer RNA (eRNA), a class of noncoding RNAs derived from enhancer regions. Transcription of developmentally regulated enhancers has been observed to be associated with their active state. The nature of transcripts (eRNA) and their functional attributes are diverse and context dependent. The majority of eRNA are nonpolyadenylated and present in low abundance owing to their low stability, and may represent transcriptional noise. However, some eRNAs have been reported to be reasonably long and stable, are enriched in nuclei, exhibit tissue‐specific expression and may contribute to enhancer function. Transcription of enhancers has been postulated to mediate enhancer function through either the act of transcription or via the transcribed RNA per se and is a useful feature to be analysed to understand mechanisms underlying enhancer activity. Enhancer Eβ at the murine TCRβ locus has been reported to exhibit enhanced occupancy of RNA polymerase II in developing thymocytes. Here, we investigated the transcriptional potential of Eβ in developing thymocytes and detected overlapping bidirectional transcripts at Eβ ranging between 0.7 and 1.7 kb. These noncoding transcripts are capped, polyadenylated, nuclear and expressed specifically in thymocytes. Delineation of these characteristics is important to further investigate their functional roles in mediating enhancer activity.